Numerical Simulation of Dust Lifting Within a Steady State Dust Devil. Issue 11 (1st November 2021) - Sheel, Varun; Uttam, Shefali; Mishra, S. K.
Abstract: On Mars, dust devils play an important role in injecting dust grains into the atmosphere. The exact amount that they contribute to the dust budget of the atmosphere is yet not clearly known. In this study, we model the spatial distribution of dust concentration within a steady state Martian dust devil for the first time. We numerically solve the equations of motion for dust particles to determine their velocity inside a dust devil, 10 m wide and 1, 000 m tall, and consequently determine the dust loading using the continuity equation. We consider an initial wind profile, which is dependent on the circulation strength of the vortex ( Γ ) and viscosity of the air ( ν ). Our simulations indicate a maximum concentration of ∼1, 400 cm −3 near the surface and at the boundary of the vortex. The larger size particles are lifted to lower heights. The radial and tangential particle velocities peak at ∼60 m, while the vertical velocity peaks at ∼100 m. A higher circulation strength ( Γ ), leads to a higher loading of dust, whereas a change in the air viscosity ( ν ) does not have a significant effect on the dust loading inside the steady state dust devil. From the simulated dust distribution in our vortex, the estimations of a dust flux of ∼5 × 10 −5 kgm −2 s −1, a total optical depth of 0.2 and a near‐surface heating rate of 0.05 Ks − 1, are consistent with observations. Our calculations can provide useful inputs to study the effect of dust devils on boundary layer processes. Plain Language Summary: Dust has a strong impact on Martian atmosphere's thermal and dynamical state, thus affecting the climate and environment of Mars. Dust laden convective vortices, called dust devils, are a source of dust injection into the atmosphere. But its quantitative contribution to the total dust loading in the atmosphere and relative dust loading within the dust devil, are not well understood. Therefore, we model the spatial distribution of dust concentration within a steady state Martian dust devil. We numerically solve the equations of motion for dust particles to determine their velocity inside the dust devil and consequently determine the dust distribution using the continuity equation. We obtain that the major loading of dust particles is near the surface and it decreases as we move higher in altitude. The larger‐sized dust particles are more concentrated toward the ground whereas, the smaller‐sized dust particles can reach up to certain heights. Moreover, the dust concentration is highest at the boundary of the dust devil and decreases as we move toward the center of the dust devil. The dust flux estimated for our dust devil, matches well with those from observations of Martian dust devils. Key Points: Spatial distribution of dust density is simulated in a steady state dust devil Our results are sensitive to vortex strength and show significant dust load up to 10 m from the surface Our calculations, including estimates of dust flux, optical depth and heating rates, are useful inputs for boundary layer studies